A Synthetic Small Molecule F240B Decreases NLRP3 Inflammasome Activation by Autophagy Induction - Wu, Chun-Hsien; Gan, Chin Heng; Li, Lan-Hui; Chang, Jen-Che; Chen, Shin-Tai; Menon, Mridula P.; Cheng, Shu-Meng; Yang, Shih-Ping; Ho, Chen-Lung; Chernikov, Oleg V.; Lin, Chi-Hung; Lam, Yulin; et al. (Frontiers in Immunology, 2020)
Conjugated polyenes are a class of widely occurring natural products with various biological functions. We previously identified 4-hydroxy auxarconjugatin B (4-HAB) as anti‐inflammatory agent with an IC50 of ~20 µM. In this study, we synthesized a new anti‐inflammatory 4-HAB analogue, F240B, which has an IC50 of less than 1 µM. F240B dose-dependently induced autophagy by increasing autophagic flux, LC3 speck formation and acidic vesicular organelle formation. F240B inhibited NACHT, LRR and PYD domain-containing protein 3 (NLRP3) inflammasome activation through autophagy induction. In a mechanistic study, F240B inhibited interleukin (IL)-1β (IL-1β) precursor expression, promoted degradation of NLRP3 and IL-1β, and reduced mitochondrial membrane integrity loss in an autophagy-dependent manner. Additionally, F240B inhibited apoptosis-associated speck-like protein containing a CARD (ASC) oligomerization and speck formation without affecting the interaction between NLRP3 and ASC or NIMA-related kinase 7 (NEK7) and double-stranded RNA-dependent kinase (PKR). Furthermore, F240B exerted in vivo anti-inflammatory activity by reducing the intraperitoneal influx of neutrophils and the levels of IL-1β, active caspase-1, IL-6 and monocyte chemoattractant protein-1 (MCP-1) in lavage fluids in a mouse model of uric acid crystal-induced peritonitis. In conclusion, F240B attenuated the NLRP3 inflammasome through autophagy induction and can be developed as an anti-inflammatory agent in the future.